Penegakan HAM terhadap dampak globalisasi yang mengancam identitas nasional - Azis, Moch. Amirul (Maliki Interdisciplinary Journal, 2026)
Globalization brings fundamental changes that affect not only economic and technological aspects but also erode the cultural dimensions and identity of a nation. Indonesia, as a multicultural country with extraordinary traditional richness, faces real challenges in maintaining its national identity amid the increasingly rapid tide of globalization. This article aims to examine how the enforcement of human rights (HAM) can serve as an important instrument in protecting national identity from the threats of globalization. This research employs a literature study approach with a conceptual analysis method of various human rights theories, globalization theories, and relevant national and international legal regulations. The findings indicate that uncontrolled globalization has the potential to erode local cultural values and weaken the sense of nationhood. However, human rights provide a strong normative framework for protecting the rights of cultural groups and strengthening national identity in an inclusive manner. The state has an obligation to enforce human rights while simultaneously protecting cultural diversity as part of its constitutional responsibilities. It is concluded that synergy between human rights enforcement and proactive cultural policies is key to facing the pressures of globalization without neglecting global openness.